The usefulness of left ventricular volume and aortic diastolic flow reversal for grading chronic aortic regurgitation severity - Using cardiovascular magnetic resonance as reference. (1st October 2021) - Gao, Sinsia A.; Polte, Christian L.; Lagerstrand, Kerstin M.; Bech-Hanssen, Odd
Abstract: Echocardiographic evaluation of chronic aortic regurgitation (AR) severity can lead to diagnostic ambiguity due to few feasible parameters or incongruent findings. The aim of the present study was to improve the diagnostic usefulness of left ventricular (LV) enlargement and aortic end-diastolic flow velocity (EDFV) using cardiovascular magnetic resonance (CMR) as reference. Patients ( n  = 120) were recruited either prospectively ( n  = 45) or retrospectively ( n  = 75). Severe AR (CMR regurgitant fraction > 33%) was present in 51% and 93% of the patients had LV ejection fraction ≥ 50%. EDFV and LV end-diastolic volume index (EDVI) were assessed by echocardiography using the traditional (excluding trabeculae) and recommended approach (including trabeculae). The patients were randomised to a derivation ( n  = 60) or a test group (n = 60). EDVI (traditional/recommended) to rule in (>99/118 ml/m 2 ) and rule out severe AR (≤75/87 ml/m 2 ) were identified using ROC analyses in the derivation group. The corresponding thresholds for EDFV were >17 cm/s and ≤10 cm/s. In the test group, the positive/negative likelihood ratios to rule in/rule out severe AR using EDVI were 10.0/0.14 (traditional), 6.2/0.11 (recommended), and using EDFV were 10.2/0.08. To rule in and rule out severe AR using derived cut-off values instead of >2 SD reduced the false positives by 92%, whereas using EDFV ≤10 cm/s instead of ≤20 cm/s reduced the false negatives by 94%. In conclusion, EDVI and EDFV as quantitative parameters are useful to rule in or rule out severe chronic AR. Importantly, other causes of LV enlargement have to be considered. Highlights: LV end-diastolic volume index (EDVI) and end-diastolic flow velocity (EDFV) are the most feasible parameters for echocardiographic grading of AR severity. Using cardiovascular magnetic resonance as reference, EDVI (by traditional/recommended approach) and EDFV to rule in and rule out severe AR were derived. In a separate test group, the usefulness of these thresholds to discriminate severe from non-severe AR was validated.